Multilocus Analysis of DNA Barcodes of matK, rbcL, and ITS in the Asteraceae Family - Rosa, Vita; Roslim, Dewi Indriyani; Herman, Herman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Asteraceae is known as compositae which is a cosmopolitan plant group consisting of approximately 1,250 genera and 25,000 species distributed in various regions. Similar morphological characters among species pose challenges in taxonomy and phylogenetics, making the identification process difficult. These limitations of morphological identification can be overcome through a molecular approach using DNA barcoding to reduce errors in species grouping and in determining phylogenetic relationships among plant species in the Asteraceae family through multilocus DNA barcode analysis of matK, rbcL and ITS. This study aims to analyze DNA barcodes matK, rbcL and ITS in the Asteraceae family. DNA sequence exploration were obtained from GenBank through the NCBI website. Analysis of DNA sequence was performed using MEGA11, and phylogenetic tree reconstruction was carried out using the Neighbor Joining (NJ) method in MEGA11 with the p-distance evolutionary model and rapid bootstrap analysis conducted with 1000 replicates. The rbcL sequence had the lowest number of variable sites (13.6%) compared to single sequences and other combinations, while ITS showed the highest number of variable sites (59.3%), and the matK+rbcL+ITS combination produced the most informative phylogenetic grouping because it provided more consistent bootstrap support at the main branches. The multilocus approach increases the resolution in describing phylogenetic relationships among genera within the family Asteraceae.